Fun or Routine? The Division of Childcare Activities between Woman and Man in the Households in Poland - Michoń , Piotr (Studia Oeconomica Posnaniensia, 2016)
When dealing with the traditional family model, the theories of time, availability, and exchange do explain the division of labour division in a household. However, recent studies expose their limitations: first, when family model is different than the traditional one, and second, when one applies the theories to the study of division of childcare in a household. The paper aims to examine the division of six various care activities (e.g. dressing, playing with a child) between the man and the woman in Polish households, varying due to the family economic model. The study shows that the fathers' share in childcare varies depending on the type of care activities. Men's involvement is greater for interactive care and smaller with regards to routines. Men are most likely to play and do homework with children, and least likely to care for sick children and assist them when dressing. Even if a man does not work, the woman often is the main performer of care activities. The results suggest that an important explanation for the behaviour of men and women is their gender identity.